EXPLORATION OF MEDICAL STUDENTS' PERCEPTION TOWARDS PBL TUTORIAL MODIFIED WITH INDIVIDUAL AND GROUP ASSESSMENT - Kristina, Tri Nur; Dinar, Kintania Lutfiah; Fauzia, Lathifa Putry; Dewi, Dian Puspita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Problem-based learning (PBL) has been implemented at the Faculty of Medicine, Universitas Diponegoro, since 2001. The model was later modified to enhance student engagement by incorporating individual and group assessment. Students are assessed not only on their knowledge but also on their skills, attitudes, and active participation in discussions, which contribute to their overall block assessment.Aims: This study explores the students’ perceptions of implementing the modified PBL.Methods: We conducted a qualitative study using six focus group discussions (FGD) involving 36 students from the 2021, 2022, and 2023 cohorts.Results: The study identified five opportunity themes and five challenge themes related to the modified PBL implementation, along with several student recommendations for improvement. The opportunities include more structured individual learning, increased active participation, group reports serving as practical and comprehensive learning resources, and the development of collaboration and leadership skills. Meanwhile, the challenges include delays in distributing PBL scenarios, an imbalance in group participation (e.g., overly passive or dominant students), the individual report becoming burdensome during exam periods, and the limited relevance of individual assessments in discussions. Nonetheless, students demonstrated awareness of these challenges and proposed constructive suggestions for improvement.Conclusion: The findings suggest that students benefit from the modified PBL in various ways. However, it can also potentially threaten the internal motivation of a self-directed learner.